Cerebellar mutism syndrome: From pathophysiology to rehabilitation - Fabozzi, Francesco; Margoni, Stella; Andreozzi, Bianca; Musci, Maria Simona; Del Baldo, Giada; Boccuto, Luigi; Mastronuzzi, Angela; Carai, Andrea (Frontiers in Cell and Developmental Biology, 2022)
Cerebellar mutism syndrome (CMS) is a common complication following surgical resection of childhood tumors arising in the posterior fossa. Alteration of linguistic production, up to muteness and emotional lability, generally reported at least 24 h after the intervention, is the hallmark of post-operative CMS. Other associated traits include hypotonia and other cerebellar motor signs, cerebellar cognitive-affective syndrome, motor deficits from the involvement of the long pathways, and cranial neuropathies. Recovery usually takes 6 months, but most children are burdened with long-term residual deficits. The pathogenic mechanism is likely due to the damage occurring to the proximal efferent cerebellar pathway, including the dentate nucleus, the superior cerebellar peduncle, and its decussation in the mesencephalic tegmentum. Proven risk factors include brain stem invasion, diagnosis of medulloblastoma, midline localization, tumor size, invasion of the fourth ventricle, invasion of the superior cerebellar peduncle, left-handedness, and incision of the vermis. Currently, rehabilitation is the cornerstone of the treatment of patients with cerebellar mutism syndrome, and it must consider the three main impaired domains, namely speech, cognition/behavior, and movement.